Improvement of thermal performance of building envelope through passive technologies - Yap, Adeline Su Jing (2014)
In this project, the author carries out both 2D and 3D investigations on the double-skin roof model in Energy Systems Lab followed by CFD simulations using ANSYS Workbench 14.5 – FLUENT. Validation is done by comparing the results from experiment and simulations. After which, parameters study will be performed, using the simulation models that have been validated. For physical experiments on the double-skin roof model, the author investigated on the effect of inclination angle, air gap height as well as air gap height to width ratio for 3D study. Heat flux of the top roof, surface temperatures of top and bottom roof, air temperature and air velocity across the air gap height are recorded. The author replicates this double-skin roof model on ANSYS Workbench 14.5 – FLUENT and achieves validation after comparing simulation results with the experimental results. Validation of CFD model justifies its use to carry out parameters study. The author examines further the effect of inclination angle and air gap height, as well as that of the absorptivity of the upper roof and implementation of radiant barrier. Lastly, the author makes a conclusion on the effectiveness of each parameter studied and identifies various areas of improvement as well as possible future work for more precise understanding of the double-skin roof in order to enhance its thermal performance.